Machine learning approach for ECG analysis and predicting different heart diseases - Tithi, Sushmita Roy; Aktar, Afifa; Aleem, Fahimul (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.